Study on the Alliance between SFCL and Hybrid DC Circuit Breaker for Protecting HVDC Grid. (June 2020) - Ayachi Amor, Yacine; Didier, Gaëtan; Leveque, Jean; Hamoudi, Farid
Abstract: Breaking the DC fault in HVDC grid is the greatest challenge for DC grid protection system. Although there are many scientific researches investigating the high voltage DC breakers, yet, there is still always a trade-off between the interruption time and the breaking capability. Therefore, combining between the superconducting fault current limiter (SFCL) technology with a fast DC circuit breaker could bring a solution to this limitation. In this work, an accurate model of resistive-type SFCL (r-SFCL) considering the electro-thermal behaviour, is proposed to be placed in series with ABB proactive hybrid DC circuit breaker (PHCB). To test the viability of the system, a pole-to-pole DC fault scenario was imposed in a HVDC grid. The numerical analysis was undertaken with (EMTP-RV®) software, while the simulation results show how effectively the SFCL can reduce the fault current below the maximum breaking capability. Also, it is concluded that there is a positive interaction between the r-SFCL and PHCB.